EFFECT OF SOME VARIBLES ON SOLIDIFICATION PROCESS OF ADHESIVE LINE USED IN WOOD STRUCTURE - A. Al-Mallah (Mesopotamia Journal of Agriculture)
This study was conducted to test the strength of glue line in wood structures by using some mechanical tests ( Dry and wet tensile tests, shear strength test). Two kinds of adhesives (Urea-formaldehyde (UF) and poly-vinyl acetate (PVA) and three types of wood surfaces (Pure Pine, Pure Sycamore and substrate of Pine with Sycamore) and two methods of adhesive curing (Electrical and microwave domestic ovens) were used. Analysis of variance results showed significant differences of (wood type, adhesive type, grain direction, curing methods and adhesive quantity) on dry and wet tensile strength after immersion in water for thirty and sixty minutes. Wood type showed that pine wood have the greatest dry and wet tensile strength followed by pine with sycamore wood and the lowest tensile strength was shown in sycamore wood. Urea-formaldehyde adhesive showed the highest value in all the studied characters as compared with poly-vinyl acetate adhesive which gave the lowest tensile strength. The parallel grain direction gave the best value as compared to vertical grain direction for both dry and wet tensile strength. Electrical oven curing method gave the best dry and wet tensile strength as compared to microwave oven. Two gram adhesive quantity gave the highest results as compared with 1.5 and 1 gm for all the studied characters, but, there were no significant differences between 2 and 1.5 gm quantity. Concerning shear strength of the adhesive line, the results showed that there were significant effects for wood type, adhesive type, curing methods and adhesive quantity on the studied shear strength. pine wood showed the best shear strength followed by pine with sycamore wood, also Urea-formaldehyde adhesive gave higher value for this character. Electrical oven curing method gave the highest shear strength value when compared with microwave oven. The study also showed that 1.5 gm quantity of adhesive gave better results shear strength followed by 1.25 and 1 gm.